Studi Komputasi Daidzein, Galangin, Genistein, Naringenin sebagai Inhibitor Korosi Besi dengan Metode DFT dan Membandingkannya dengan Luteolin - Yeni Stiadi; Muhammad Ilham; Emriadi (Departemen Kimia Universitas Andalas, 2022)
Corrosion inhibitors of daidzein, galangin, genistein, naringenin and luteolin compounds have been studied using the Density Functional Theory (DFT) method with the basis set B3LYP/6-31G using the Gaussian program. To prevent corrosion, organic inhibitors are needed which are safe for the environment. Therefore, researchers are looking for other organic inhibitors that have the potential to prevent corrosion. The calculated quantum chemical parameters are EHOMO, ELUMO, gap energy (∆E), ionization potential (I), electron affinity (A), electronegativity (X), hardness (ɳ), softness (σ), electrophilicity (ω), nucleophilicity (ε), mulliken charge density, back-donation energy (Eb-d), electron transfer (∆N), adsorption energy (Eads), and bond energy (Ebinding). Theoretical calculations show that naringenin is a good inhibitor compared to other compounds so that it can be used as an alternative organic inhibitor to replace luteolin. In this research, naringenin is a compound that has the potential as an inhibitor as seen from the structure and parameter calculations that have been carried out, so that naringenin can be used as an organic inhibitor to replace luteolin. The theoretical order of increasing inhibition is naringenin > genistein > galangin > daidzein. This theoretical study will greatly contribute to the experimental research of organic inhibitors because the theoretical increase in inhibition is already known.